2020
DOI: 10.4103/jcd.jcd_405_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of antibacterial efficacy of Allium sativum extract, aqueous ozone, diode laser, and 3% sodium hypochlorite in root canal disinfection: An in vivo study

Abstract: Aim: The present study aimed to individually evaluate and compare the aerobic and anaerobic antibacterial activity of Allium sativum extract, aqueous ozone, diode laser, and 3% sodium hypochlorite (NaOCl) as root canal irrigants. Materials and Methods: Forty-eight patients were selected and randomly allocated to one of the four groups ( n = 12 each) according to the irrigant to be used in each group. For each include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…26,33,34,36 In contrast, some other studies indicated that the diode laser is effective and acceptable when used solely. 12,19,20 Moreover, when Er, Cr: YSGG is utilized solely, it does not eradicate root canal bacteria effectively; however, using this laser with LAI technique with silver nanoparticles, NaOCl or saline showed acceptable outcomes in disinfecting the root canal system. 21,37,45,50 The Nd: YAG laser has been used only in conjunction with silver nanoparticles and saline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,33,34,36 In contrast, some other studies indicated that the diode laser is effective and acceptable when used solely. 12,19,20 Moreover, when Er, Cr: YSGG is utilized solely, it does not eradicate root canal bacteria effectively; however, using this laser with LAI technique with silver nanoparticles, NaOCl or saline showed acceptable outcomes in disinfecting the root canal system. 21,37,45,50 The Nd: YAG laser has been used only in conjunction with silver nanoparticles and saline.…”
Section: Discussionmentioning
confidence: 99%
“…14,[16][17][18] However, some studies have reported that merely irradiating the root canal with a diode laser reduces the bacterial load more than traditional irrigation methods. 13,[19][20][21][22][23][24][25] To achieve higher levels of disinfection, the diode laser has been used coincide with irrigation with distilled water, 26,27 ozonated water, 26 saline, 12,22 chlorhexidine, 27 silver nanoparticles, 27 and another laser application. 28 Additionally, the diode laser has been used in the LAI technique with NaOCl, 13,29,30 and most of these studies have reported that LAI is a more potent tactic to disinfect root canals.…”
Section: Diodementioning
confidence: 99%
“…With the aid of the CAB technique, this powerful technique can be used safely even in cases of teeth with open apices. [ 2 14 22 23 24 25 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was interesting to use its extract in root canal disinfection protocols. Previous studies (Elheeny, 2019; Ghoddusi et al, 2021; Mehta et al, 2020) used Allium sativum as an irrigant and showed promising clinical results. However, according to our knowledge, it is not clear whether the AS extracts' usage as an intracanal medicament could give more antibacterial action than the traditionally used calcium hydroxide or not.…”
Section: Introductionmentioning
confidence: 99%